2008
DOI: 10.1007/s10509-008-9867-7
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type-I string cosmological models in bimetric theory of gravitation

Abstract: Bianchi type-I string cosmological models are obtained in bimetric theory of gravitation proposed by Rosen (Gen. Relativ. Gravit. 4:435, 1973). Established the existence of string cosmological models, unlike the earlier authors, in this theory and studied some physical and geometrical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The Bianchi I geometry has been studied in several contexts beyond general relativity [19][20][21][22][23]. Such a geometry generalizes the flat Friedmann-Lemaître-Robertson-Walker (FLRW) adopted in the standard model.…”
Section: Introductionmentioning
confidence: 99%
“…The Bianchi I geometry has been studied in several contexts beyond general relativity [19][20][21][22][23]. Such a geometry generalizes the flat Friedmann-Lemaître-Robertson-Walker (FLRW) adopted in the standard model.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [16] have investigated the variation law for Hubble's parameter in a homogeneous and anisotropic Bianchi type-V space time model that yield a constant value of deceleration parameter. Bianchi type-V cosmological models with negative deceleration parameter in scalar tensor theories have been presented by Rao et al [17][18][19]. Very recently, Singh and Baghel [20] have studied the Bianchi type-V model with constant deceleration parameter in general relativity and Ram et al [21] have studied such type of models in Saez-Ballester theory.…”
mentioning
confidence: 99%
“…Sahoo [27] has shown that the spherically symmetric cosmological model did not exist in Rosen's bimetric theory of gravitation when the source of gravitation was either perfect fluid or massive string whereas the model did exist in scalar meson field. Rao et al [28] have studied Bianchi type-I string cosmological models in bimetric theory of gravitation. Recently, Sahoo [29] has discussed inhomogeneous plane symmetric string cosmological models in bimetric theory of gravitation.…”
Section: S D Katore R S Rane and K S Wankhadementioning
confidence: 99%